Systematic review of suicide in economic recession - Oyesanya, Mayowa (World J Psychiatry, 2015)
AIM: To provide a systematic update of the evidence concerning the relationship between economic recession and suicide. METHODS: A keyword search of Ovid Medline, Embase, Embase Classic, PsycINFO and PsycARTICLES was performed to identify studies that had investigated the association between economic recession and suicide. RESULTS: Thirty-eight studies met predetermined selection criteria and 31 of them found a positive association between economic recession and increased suicide rates. Two studies reported a negative association, two articles failed to find such an association, and three studies were inconclusive. CONCLUSION: Economic recession periods appear to increase overall suicide rates, although further research is warranted in this area, particularly in low income countries.